The Effect of Self-Efficacy and Organizational Culture on The Public Elementary School Teachers’ Achievement Motivation - Irah Sumirah; Ajat Sudrajat; Amalia Sapriati (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Achievement motivation is an essential aspect that can encourage teachers to do things related to educational progress as best as possible. Teacher achievement motivation can be influenced by self-efficacy and organizational culture. High self-efficacy can increase teachers’ confidence in their abilities to be ready to face various things on their assignments. Besides, organizational culture is crucial for teachers to create a conducive work environment to feel comfortable doing their duties. This study aimed to determine to analyze the influence of self-efficacy and organizational culture on teacher achievement motivation. This study was conducted on public elementary school teachers in Kramatwatu Subdistrict, Serang Regency, with a population of 193 and a sample of 130 respondents using a simple random sampling method. The influence was measured by the correlation and regression formula. The multiple regression results showed the equation Y = 35.014+0.311X1+0.378X2+↋. It indicated that self-efficacy increased teacher achievement motivation by 0.311 units. It signified that simultaneously, self-efficacy and organizational culture influenced teacher achievement motivation, with a contribution of 11.3%. Based on these results, the education office, school, and other related parties need to make efforts to increase self-efficacy and organizational culture so that teacher achievement motivation can also increase.